2021
DOI: 10.1038/s41467-021-26059-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of patient-derived PDAC organoids reveals cell state heterogeneity and a conserved developmental hierarchy

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is projected to be the second leading cause of cancer mortality by 2030. Bulk transcriptomic analyses have distinguished ‘classical’ from ‘basal-like’ tumors with more aggressive clinical behavior. We derive PDAC organoids from 18 primary tumors and two matched liver metastases, and show that ‘classical’ and ‘basal-like’ cells coexist in individual organoids. By single-cell transcriptome analysis of PDAC organoids and primary PDAC, we identify distinct tumor cell states … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 56 publications
5
69
0
Order By: Relevance
“…The next wave of studies anticipated in the near future will undoubtedly shed further light on which model systems and assays carry the greatest predictive power. Several published studies have described the composition and transcriptional evolution of PDAC organoids and primary tumors at a single-cell resolution [57,71,74,101]. However, these studies have not yet revealed the extent to which subclonal resistance mechanisms contributing to tumor escape occur and could be identified at baseline or emerge as a response to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next wave of studies anticipated in the near future will undoubtedly shed further light on which model systems and assays carry the greatest predictive power. Several published studies have described the composition and transcriptional evolution of PDAC organoids and primary tumors at a single-cell resolution [57,71,74,101]. However, these studies have not yet revealed the extent to which subclonal resistance mechanisms contributing to tumor escape occur and could be identified at baseline or emerge as a response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Specific CAF subsets were also found to associate with immunotherapy responses [72,73]. Because PDOs generally lack stromal cells [74], numerous studies have focused on developing co-culture models, which could better depict the tumor microenvironment and interactions between ductal and stromal cells. Co-culture models could also aid in drug screening for stroma-targeting agents and immunotherapies.…”
Section: Co-culturesmentioning
confidence: 99%
“…Some studies have adapted the original PDAC-organoid media composition ( Boj et al, 2015 ) to generate PDOs ( Huang et al, 2015 ; Seino et al, 2018 ; Driehuis et al, 2019 ; Krieger et al, 2021 ). Although finding a consensus media to unify and standardize PDO growth across laboratories seems desirable, defining a unique media might be, in this case, delicate.…”
Section: Pancreatic Cancer Derived Organoidsmentioning
confidence: 99%
“…Mucin secretion is the main characteristic of PDAC precursor lesions (IPMNs) ( 153 ). Mucins are also highly expressed in PDAC TME; in fact, most of the recent studies that utilized scRNA-seq to characterize PDAC samples identified a cluster of mucin-producing cells especially in the patients with a more aggressive disease ( 51 , 154 , 155 ). This evidence suggests that mucins play a major role in PDAC carcinogenesis, not only supporting PDAC development by activating several oncogenic pathways, but also sustaining cancer cells to escape the immune surveillance by multiple mechanisms.…”
Section: The Emerging Role Of Ecm Components In Immune Escapingmentioning
confidence: 99%